Effectiveness of Diabetes Self-Management Education Programs for US Latinos at Improving Emotional Distress: A Systematic Review. Issue 1 (February 2019) - Gutierrez, Angela P.; Fortmann, Addie L.; Savin, Kimberly; Clark, Taylor L.; Gallo, Linda C.
Purpose: This systematic review examined whether diabetes self-management education (DSME) interventions for US Latino adults improve general emotional distress (eg, depression symptoms) and/or health-specific emotional distress (eg, diabetes distress). The topic is important given the high prevalence of type 2 diabetes (T2DM), concomitant distress, and worse health outcomes among Latinos and considering the barriers that distress poses for effective diabetes self-management. Methods: Following PRISMA guidelines, a search of the online databases PsycINFO, CINAHL, PubMed, and CENTRAL was conducted from database inception through April 2018. A comprehensive search strategy identified trials testing DSME interventions for US Latinos with T2DM that reported on changes in general or health-specific emotional distress. Risk of bias was assessed using the EPHPP Quality Assessment Tool. Raw mean differences ( D ) and effect sizes ( d ) were computed where possible. Results: Fifteen studies were included in the review. Six of 8 studies that examined depression symptoms reported significant symptom reduction. Of 10 studies that examined health-specific emotional distress, 6 reported significant symptom reduction. Effect sizes ranged from −0.20 to –3.85. Null findings were more readily found among studies with very small sample sizes (n < 30) and studies testing interventions without specific psychosocial content, with little cultural tailoring, with less frequent intervention sessions, and with support sessions lacking concurrent diabetes education. Most studies (11) received a weak rating of evidence quality. Conclusions: There is an absence of strong evidence to support that DSME programs tailored for Latino adults with T2DM are beneficial for improving emotional distress. Methodologically robust studies are needed.